CRISPR‐LbCas12a‐mediated modification of citrus. Issue 10 (10th April 2019) - Jia, Hongge; Orbović, Vladimir; Wang, Nian
Summary: Recently, CRISPR‐Cas12a (Cpf1) from Prevotella and Francisella was engineered to modify plant genomes. In this report, we employed CRISPR‐LbCas12a (LbCpf1), which is derived from Lachnospiraceae bacterium ND2006, to edit a citrus genome for the first time. First, LbCas12a was used to modify the CsPDS gene successfully in Duncan grapefruit via Xcc‐facilitated agroinfiltration. Next, LbCas12a driven by either the 35S or Yao promoter was used to edit the PthA4 effector binding elements in the promoter (EBEP thA4 ‐CsLOBP) of CsLOB1 . A single crRNA was selected to target a conserved region of both Type I and Type II CsLOBPs, since the protospacer adjacent motif of LbCas12a (TTTV) allows crRNA to act on the conserved region of these two types of CsLOBP. CsLOB1 is the canker susceptibility gene, and it is induced by the corresponding pathogenicity factor PthA4 in Xanthomonas citri by binding to EBEP thA4 ‐CsLOBP. A total of seven 35S‐LbCas12a‐transformed Duncan plants were generated, and they were designated as #D35 s1 to #D35 s7, and ten Yao‐LbCas12a‐transformed Duncan plants were created and designated as #Dyao 1 to #Dyao 10. LbCas12a‐directed EBEP thA4 ‐CsLOBP modifications were observed in three 35S‐LbCas12a‐transformed Duncan plants (#D35 s1, #D35 s4 and #D35 s7). However, no LbCas12a‐mediated indels were observed in the Yao‐LbCas12a‐transformed plants. Notably, transgenic line #D35 s4, which contains the highest mutation rate, alleviates XccΔpthA4:dCsLOB1.4 infection. Finally, no potential off‐targets were observed. Therefore, CRISPR‐LbCas12a can readily be used as a powerful tool for citrus genome editing.